COSMIC’s Large-scale Search for Technosignatures during the VLA Sky Survey: Survey Description and First Results - C. D. Tremblay; J. Sofair; L. Steffes; T. Myburgh; D. Czech; P. B. Demorest; R. A. Donnachie; A. W. Pollak; M. Ruzindana; Siemion A. P. V.; S. S. Varghese; S. Z. Sheikh (The Astronomical Journal, 2025)
Developing algorithms to search through data efficiently is a challenging part of searching for signs of technology beyond our solar system. We have built a digital signal processing system and computer cluster on the backend of the Karl G. Jansky Very Large Array (VLA) in New Mexico in order to search for signals throughout the Galaxy consistent with our understanding of artificial radio emissions. In our first paper, we described the system design and software pipelines. In this paper, we describe a postprocessing pipeline to identify persistent sources of interference, filter out false positives, and search for signals not immediately identifiable as anthropogenic radio frequency interference during the VLA Sky Survey. As of 2024 September 1, the Commensal Open-source Multi-mode Interferometric Cluster had observed more than 950,000 unique pointings. This paper presents the strategy we employ when commensally observing during the VLA Sky Survey and a postprocessing strategy for the data collected during the survey. To test this postprocessing pipeline, we searched toward 511 stars from the Gaia catalog with coherent beams. This represents about 30 minutes of observation during the VLA Sky Survey, where we typically observe about 2000 sources hr ^–1 in the coherent beamforming mode. We did not detect any unidentifiable signals, setting isotropic power limits ranging from 10 ^11 to 10 ^16 W.